2018
DOI: 10.2967/jnumed.117.206375
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dedicated Rebinner with Rigid Motion Correction for the mMR PET/MR Scanner, and Validation in a Large Cohort of 11C-PIB Scans

Abstract: Head motion occurring during brain PET studies leads to image blurring and to bias in measured local quantities. The objective of this work was to implement a correction method for PET data acquired with the mMR synchronous PET/MR scanner. A list-mode-based motion-correction approach has been designed. The developed rebinner chronologically reads the recorded events from the Siemens list-mode file, applies the estimated geometric transformations, and frames the detected counts into sinograms. The rigid-body mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…For MACC PET data, motion correction was performed prior to tomographic reconstruction into a single static frame, using an in‐house developed rebinner with rigid motion correction, binning into 20s frames (Reilhac et al, ). Motion corrected images were reconstructed into a volume of 344 × 344 × 344 voxels (voxel size = 2.09 × 2.09 × 2.03 mm 3 ) using 3D Ordinary Poisson Ordered‐subsets Expectation Maximization algorithm (Panin, Kehren, Michel, & Casey, ) with all corrections performed (including resolution modeling) and using three iterations and 21 subsets.…”
Section: Methodsmentioning
confidence: 99%
“…For MACC PET data, motion correction was performed prior to tomographic reconstruction into a single static frame, using an in‐house developed rebinner with rigid motion correction, binning into 20s frames (Reilhac et al, ). Motion corrected images were reconstructed into a volume of 344 × 344 × 344 voxels (voxel size = 2.09 × 2.09 × 2.03 mm 3 ) using 3D Ordinary Poisson Ordered‐subsets Expectation Maximization algorithm (Panin, Kehren, Michel, & Casey, ) with all corrections performed (including resolution modeling) and using three iterations and 21 subsets.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects underwent a 30-min PET scan on the 3 T Biograph mMR (Siemens Healthcare GmbH) at the Clinical Imaging Research Centre (CIRC), 40 min after injection of 370 (± 15%) MBq of [ 11 C]PiB. Each PET listmode datum was motion-corrected using an in-house developed rebinner [20] and reconstructed into a 3D matrix of 344 × 344 × 127 with voxel size of 2.09 × 2.09 × 2.03 mm 3 . 3D ordinary Poisson ordered-subsets expectation maximization with resolution modeling using 3 iterations and 21 subsets was applied with all corrections.…”
Section: Participants Neuropsychological Examination and Neuroimagingmentioning
confidence: 99%
“…MRI provides high brain soft-tissue contrast and temporal resolution, which makes it ideal for demonstrating the dynamic head motion. With the involvement of PET and MRI dual-modalities in brain imaging, MRI-driven MC (MRMC) for voluntary head motion during a lengthy PET study can be crucial in maintaining the alignment between a series of PET and MRI images (Reilhac et al, 2018). Hybrid PET/MRI system allows for acquiring MRI images with dynamically changing anatomy at well as list-mode PET acquisition.…”
Section: Mri-based MCmentioning
confidence: 99%
“…Several researchers suggested that direct reconstruction using event-by-event motion correction for dynamic brain PET is achievable and robust (Germino et al, 2017; Jiao et al, 2017). On the other hand, accurate MC may be achieved at a cost of resolution loss to some extent (Reilhac et al, 2018). These issue may also be solved by the combination of MRI navigator sequence and optical motion tracking system, which complement each other’s advantages.…”
Section: Future Perspectivementioning
confidence: 99%